4
$\begingroup$

I've been trying to show that $$\ln(\sec 3t+\tan 3t)=2\tanh^{-1}(\tan(3t/2))$$

I used the identity $$\tanh^{-1}x=\frac12\ln\frac{1+x}{1-x}$$ to write: $$\begin{array}{tcl} 2\tanh^{-1}(\tan(3t/2))&=&2\cdot\frac12\ln\dfrac{1+\tan(3t/2)}{1-\tan(3t/2)}\\ 2\tanh^{-1}(\tan(3t/2))&=&\ln\dfrac{1+\tan(3t/2)}{1-\tan(3t/2)}\\ \end{array}$$ Then I used $$\tan\frac{\theta}{2}=\frac{1-\cos \theta}{\sin\theta}$$ to write: $$\begin{array}{tcl} 2\tanh^{-1}(\tan(3t/2))&=&\ln\dfrac{1+\dfrac{1-\cos3t}{\sin3t}}{1-\dfrac{1-\cos 3t}{\sin 3t}}\\ 2\tanh^{-1}(\tan(3t/2))&=&\ln\dfrac{\sin 3t+1-\cos 3t}{\sin 3t-1+\cos 3t} \end{array}$$

Now, in order to show that $$\ln(\sec 3t+\tan 3t)=\ln\dfrac{\sin 3t+1-\cos 3t}{\sin 3t-1+\cos 3t}$$ I need to show that $$\sec 3t+\tan 3t=\dfrac{\sin 3t+1-\cos 3t}{\sin 3t-1+\cos 3t}$$ Now, $$\begin{array}{tcl} \sec3t+\tan3t&=&\dfrac{1}{\cos 3t}+\dfrac{\sin 3t}{\cos 3t}\\ \sec3t+\tan3t&=&\dfrac{1+\sin 3t}{\cos 3t} \end{array}$$

Now, I am stuck. How do I show that: $$\frac{\sin 3t+1-\cos 3t}{\sin 3t-1+\cos 3t}=\frac{1+\sin 3t}{\cos 3t}$$ Here is some Matlab code that seemingly verifies the identity.

t=linspace(-1.5,1/2,1000);
y1=(sin(3*t)+1-cos(3*t))./(sin(3*t)-1+cos(3*t));
y2=(1+sin(3*t))./cos(3*t);
plot(t,y1,'b','LineWidth',4),hold on
plot(t,y2,'r','LineWidth',2)
hold off

And the image. enter image description here

$\endgroup$
3
$\begingroup$

You're almost there. To prove $$\frac{\sin 3t+1-\cos 3t}{\sin 3t-1+\cos 3t}=\frac{1+\sin 3t}{\cos 3t},$$ you need $$(\sin 3t+1-\cos 3t)\cos 3t=(\sin 3t-1+\cos 3t)(1+\sin 3t).$$ Expand it: $$\sin 3t\cos 3t+\cos 3t-\cos^2 3t=\sin 3t-1+\cos 3t+\sin^2 3t-\sin 3t+\cos 3t\sin 3t,$$ which can be simplified to $$\cos^23t+\sin^2 3t=1.$$

$\endgroup$
  • $\begingroup$ I'd like to thank your for your assistance $\endgroup$ – David Aug 28 '18 at 16:42
2
$\begingroup$

You want to prove the identity $$\ln(\sec 3t+\tan 3t)=2\tanh^{-1}(\tan(3t/2))$$

We differentiate both sides and show that the derivatives are the same.

Note that $$ \frac {d}{dt} \ln(\sec 3t+\tan 3t) = 3 \sec 3t$$

Also we have $$ \frac {d}{dt} 2\tanh^{-1}(\tan (3t/2))$$

$$=\frac {2\sec ^ 2 ( 3t/2)}{1-\tan ^2 (3t/2)} (3/2)=3 \sec 3t$$

Thus the differennce of the two functions is a constant.

Upon evaluating the functions at $t=0$ we obtain the identity.

$\endgroup$
  • $\begingroup$ I'd like to thank your for your assistance $\endgroup$ – David Aug 28 '18 at 16:43
  • $\begingroup$ Thank for your attention and understanding. $\endgroup$ – Mohammad Riazi-Kermani Aug 28 '18 at 18:51

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.